Association of biological antirheumatic therapy with risk for type 2 diabetes: a retrospective cohort study in incident rheumatoid arthritis - Attila Pethö-Schramm; Sara Gale; Khaled Sarsour; Sanjoy K Paul; Olga Montvida; Jennie H Best (BMJ Open)
Objective To explore possible associations of treatment with biological disease-modifying antirheumatic drugs (bDMARDs), including T-cell-based and interleukin-6 inhibition (IL-6i)-based therapies, and the risk for type 2 diabetes mellitus (T2DM) in patients with rheumatoid arthritis (RA).Study design, setting and participants Five treatment groups were selected from a United States Electronic Medical Records database of 283 756 patients with RA (mean follow-up, 5 years): never received bDMARD (No bDMARD, n=125 337), tumour necrosis factor inhibitors (TNFi, n=34 873), IL-6i (n=1884), T-cell inhibitors (n=5935) and IL-6i+T cell inhibitor abatacept (n=1213). Probability and risk for T2DM were estimated with adjustment for relevant confounders.Results In the cohort of 169 242 patients with a mean 4.5 years of follow-up and a mean 641 200 person years of follow-up, the adjusted probability of developing T2DM was significantly lower in the IL-6i (probability, 1%; 95% CI 0.6 to 2.0), T-cell inhibitor (probability, 3%; 95% CI 2.3 to 3.3) and IL-6i+T cell inhibitor (probability, 2%; 95% CI 0.1 to 2.9) groups than in the No bDMARD (probability, 5%; 95% CI 4.6 to 4.9) and TNFi (probability, 4%; 95% CI 3.7 to 4.7) groups. Compared with No bDMARD, the IL-6i and IL-6i+T cell inhibitor groups had 37% (95% CI of HR 0.42 to 0.96) and 34% (95% CI of HR 0.46 to 0.93) significantly lower risk for T2DM, respectively; there was no significant difference in risk in the TNFi (HR 0.99; 95% CI 0.93 to 1.06) and T-cell inhibitor (HR 0.96; 95% CI 0.82 to 1.12) groups.Conclusions Treatment with IL-6i, with or without T-cell inhibitors, was associated with reduced risk for T2DM compared with TNFi or No bDMARDs; a less pronounced association was observed for the T-cell inhibitor abatacept.